DEPICTION OF ANXIETY THROUGH METAPHORICAL SYMBOLS IN BILLIE EILISH’ SELECTED SONGS: A PSYCHOANALYTIC PERSPECTIVE - Putri Ayienda Dinanti; Indahjuli Arti (Prodi Sastra Inggris UKI, 2025)
Anxiety disorders are psychological illnesses that affect a person's ability to function normally. If not treated properly, anxiety can develop into more serious mental illnesses such as depression. This psychological phenomenon is often explored in contemporary art forms, such as literature and music. One musician named Billie Eilish, who is known for her dark and passionate songs, often explores the theme of anxiety in her work. This research aims to examine the depiction of anxiety in Billie Eilish's Hit Me Hard and Soft album. The metaphorical symbols contained in the lyrical structure are found and analysed. Then, Psychoanalysis Theory by Sigmund Freud is used to show the manifestations of anxiety in the lyrics and how they relate to the themes of anxiety, uncertainty, and internal conflict. The method used in this research is qualitative research. It is used to analyse the lyrics of the selected songs, namely: Chihiro, Wildflower, Blue, and Bittersuite. The result of this research shows that there are indeed depictions of anxieties related to loss of beloved, uncontrolled thoughts, dilemma of desire and fear of living shown in Billie Eilish's music. This research highlights how music serves as a medium to reflect and address the emotions people often experience.